Spatial Mapping of Dissolved Gases in the Danube Delta Reveals Intense Plant-Mediated Gas Transfer - Maier, Marie-Sophie; Canning, Anna R.; Brennwald, Matthias S.; Teodoru, Cristian R.; Wehrli, Bernhard (Frontiers in Environmental Science, 2022)
Global estimates see river deltas and estuaries contributing about equally to CO2 and CH4 emissions as lakes and reservoirs, despite a factor 6 smaller surface area. Assessing the horizontal gradients in dissolved gas concentrations from large river reaches to connecting canals and wetland lakes remains a challenge in many deltaic systems. To elucidate the processes affecting local CO2 and CH4 concentrations in the Romanian part of the Danube Delta, we mapped dissolved O2, N2, He and Ar using a portable gas-equilibration membrane-inlet mass spectrometer (GE-MIMS), along with CO2, CH4, water temperature and conductivity. We measured the concentrations along the aquatic continuum from a small houseboat during two campaigns, in spring and autumn, to capture different hydrological and plant growth conditions. Delta-scale concentration patterns were comparably stable across seasons. Small connecting channels were highly influenced by the riparian wetland, which was strongest in the eastern part of the biosphere reserve. These sites represented the delta’s CO2 and CH4 hotspots and showed clear signs of excess air, i.e. supersaturation of dissolved noble gases with respect to air-saturated water. As the adjacent wetland was permanently inundated, this signal was likely caused by root aeration of Phragmites australis, as opposed to traditional excess air formation via water table fluctuations in the unsaturated zone. The special vegetation setting with reed growing on floating peat coincided with the highest CO2 and CH4 concentrations (> 700 µmol/L CO2 and 13 µmol/L CH4, respectively) observed in an adjacent channel. Shallow lakes, on the other hand, were major sites of photosynthetic production with O2 oversaturation reaching up to 150 % in spring. The observed deficit in non-reactive gases (He, Ar and N2) indicated that the lakes were affected by O2 ebullition from macrophytes, reducing O2 concentrations by up to 2 mg/L. This study highlights the effect of plant-mediated gas transfer on dissolved gas concentrations and supports recent studies stressing the need to account for ebullitive gas exchange when assessing metabolism parameters from O2 in shallow, productive settings.